Cycloisomerization of Conjugated Trienones and Isomeric 2 H -Pyrans: Unified Strategy toward Cyclopenta[ b ]furans - Riveira, Martín Jorge (2015)
Conjugated trienones and isomeric 2H-pyrans were found to engage in a novel cycloisomerization cascade toward cyclopenta[b]furan derivatives. Knoevenagel chemistry and pericyclic reactions meet again to expand the polyene-carbonyl manifold.